Influence of high temperature on the residual physical and mechanical properties of foamed concrete. (15th March 2017) - Tan, Xianjun; Chen, Weizhong; Wang, Jiuhong; Yang, Diansen; Qi, Xianyin; Ma, Yongshang; Wang, Xu; Ma, Shaosen; Li, Changjun
Highlights: The appearances for all samples were not changed obviously when the temperature lower than 200 °C. With the increasing of temperature, the density became lower and lower for all samples. A function among compressive strength, temperature and density was obtained. A prediction model to reflect the change law of elastic modulus with the densities and temperatures was deduced. Abstract: To study the influence of high temperature on the properties of foamed concrete, four densities of foamed concrete (300 kg/m 3, 450 kg/m 3, 600 kg/m 3 and 800 kg/m 3 ) were taken into account in a series of tests. The change laws of appearance, mass, compressive strength and elastic module at ambient temperature and after undergoing different high temperatures (200 °C, 400 °C and 600 °C) were presented. The results indicate that the appearances for all of four different densities were different. The cracks to be observed at the higher densities foamed concretes (i.e., 800 kg/m 3 and 600 kg/m 3 ). However, the pore connectivity and surface spalling phenomenon are easier to be observed at lower densities foamed concretes (i.e., 300 kg/m 3 and 450 kg/m 3 ). With temperature increasing, the density, compressive strength and elastic modulus became lower and lower for all samples, however some details are different. Furthermore, two predicting models to reflect the change laws of compressive strength and elastic modulus with different densities and temperatures are obtained and are verified by comparing the results with the experimental data and other proposed models in previous works.